1976
DOI: 10.1139/v76-147
|View full text |Cite
|
Sign up to set email alerts
|

New reactions of 2-substituted indoles

Abstract: 2-Alkyl (or aryl) indoles react readily with phenylhydrazine in hydrochloric–acetic acid to give o-aminophenylpyrazoles 7, if the 2-substituent is of small or moderate size, or else 3-aminoindoles, if the 2-substituent is sufficiently bulky. The 3-aminoindoles readily undergo oxidative dimerization to indolylidene aminoindoles [Formula: see text] Evidence is provided for the mechanisms of formation of these two kinds of products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…402 Bergman found that 2-ethylindole reacts with N,N-dimethylacetamide dimethylacetal 179 to yield BIM 180 in the absence of a catalyst (Scheme 64). 355 Also 2-methylindole with ethyl acetate and sodium ethoxide, 403 when refluxed in acetyl chloride 404,405 or in acetyl cyanide and ethanolic potassium hydroxide 406,407 gives the BIM 181 (eq 1). The same structure was also reported from the reaction of indole and acetic anhydride in acetic acid.…”
Section: 3′-bims From Indoles Reacting With Other Functional Groupsmentioning
confidence: 99%
“…402 Bergman found that 2-ethylindole reacts with N,N-dimethylacetamide dimethylacetal 179 to yield BIM 180 in the absence of a catalyst (Scheme 64). 355 Also 2-methylindole with ethyl acetate and sodium ethoxide, 403 when refluxed in acetyl chloride 404,405 or in acetyl cyanide and ethanolic potassium hydroxide 406,407 gives the BIM 181 (eq 1). The same structure was also reported from the reaction of indole and acetic anhydride in acetic acid.…”
Section: 3′-bims From Indoles Reacting With Other Functional Groupsmentioning
confidence: 99%
“…The background reactions were further reduced by changingt he reductant to manganese powder (41 %y ield, entry 3). We also briefly investigated other catalyst precursors, all of whichg ave inferiorr e-sults (entries [4][5][6][7][8][9]. Again, no product was observed in the absence of the catalyst (entry 10).…”
Section: -Iminoindolinesmentioning
confidence: 99%
“…These compounds tend to undergo oxidatived imerization or similard ecompositionr eactions, are sensitive to light and air,a nd cannotb ep urified by chromatography. [3,4] As aconsequence, the major approaches have remained the tradi-tional indole nitration and azidation reactions followed by reductiont ot he free amine [3] and ionic cyclization reactions. [1,2,5] Modern catalytic methods, on the other hand, give rise to electron-poora nd/or protected derivatives that require deprotection or subsequent functional group interconversion steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,1‐Bis(2‐phenyl‐3‐indolyl)ethylene ( 4a ) was synthesized conventionally by refluxing 2‐phenylindoles and acetyl chloride (RANKEM, Gurugram, Haryana, India) in alcohol for 4–5 h . To explore the versatility of the procedure, we have reacted of various substituted‐2‐phenylindoles ( 1a–e ) with acetyl chloride in the presence of ZnO nanocatalyst via two approaches, that is, classical and green grindstone mechanochemical route.…”
Section: Introductionmentioning
confidence: 99%